Safety and efficacy of eltrombopag in patients with aplastic anemia: a systematic review and meta-analysis of randomized controlled trials - Huaipeng Guo; Cangchun Liu; Lei Kang; Cong Liu; Ying Liu (Hematology)
Objective This article conducts a systematic review of eltrombopag combined with immunosuppressive therapy for the treatment of aplastic anemia (AA), to demonstrate the effectiveness and safety of eltrombopag.Methods PubMed, Cochrane Library, Embase, OVID, Web of Science, China National Knowledge Infrastructure, and Wanfang databases were searched. Studies that met the inclusion criteria were collected, ranging from the establishment of the database to August 2023. Two reviewers performed meta-analyses using the Cochrane systematic review method and RevMan 5.3 software.Results This meta-analysis enrolled 5 studies with a total of 542 AA patients, including 274 in the experimental group and 268 in the control group. Meta-analyses were performed for efficacy and adverse reactions. The endpoint of effects included 6-month complete response (CR), 6-month partial response (PR), and 6-month overall response (OR). Eltrombopag combined with immunotherapy showed significant improvements in 6-month CR (OR: 2.20; 95% CI;1.54–3.12; P < 0.0001) and 6-month OR (OR = 3.66, 95% CI 2.39–5.61, P < 0.001)compared to immunosuppressive therapy for AA patients. In terms of safety, eltrombopag combined with immunosuppressive therapy showed significantly increased pigment deposition and abnormal liver function compared to immunosuppressive therapy alone.Conclusion Compared to immunosuppressive therapy alone, eltrombopag combined with immunosuppressive therapy showed significant improvements in 6-month CR and 6-month OR. However, it also resulted in increased pigment deposition and abnormal liver function in terms of safety.